2014
DOI: 10.1007/s10508-014-0357-4
|View full text |Cite
|
Sign up to set email alerts
|

Unprotected Sexual Practices Among Men Who Have Sex with Women and Men Who Have Sex with Men Living with HIV/AIDS in Rio de Janeiro

Abstract: Combined antiretroviral therapy is now acknowledged for preventing new HIV infections, besides decreasing mortality and morbidity. However, in many Latin America countries the epidemic is still driven by unprotected sexual intercourse. This study aims to describe sexual practices related to HIV/STD and to evaluate factors associated to unprotected sex among men who have sex with women (MSW) and men who have sex with men (MSM) under care at a reference center for HIV in Rio de Janeiro, Brazil. A cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 54 publications
3
8
1
3
Order By: Relevance
“…It has been suggested that frequent alcohol and drug use are common in urban gay male culture [59]. Contrary to the several studies that have found alcohol use at least once a week [55] or excess alcohol consumption [54,60] related to unsafe sexual practices in MSM, we found no association in our study. Our results, however, are closer to those of a meta-analysis not specific to MSM that found drinking alcohol was unrelated to condom use [61] and Peruvian study of MSM finding a non-significant association between problem drinking and receptive or insertive anal intercourse in the last 6 months [62].…”
Section: Discussioncontrasting
confidence: 99%
“…It has been suggested that frequent alcohol and drug use are common in urban gay male culture [59]. Contrary to the several studies that have found alcohol use at least once a week [55] or excess alcohol consumption [54,60] related to unsafe sexual practices in MSM, we found no association in our study. Our results, however, are closer to those of a meta-analysis not specific to MSM that found drinking alcohol was unrelated to condom use [61] and Peruvian study of MSM finding a non-significant association between problem drinking and receptive or insertive anal intercourse in the last 6 months [62].…”
Section: Discussioncontrasting
confidence: 99%
“…More recently, in the TEMPRANO-ANRS12136 trial of immediate versus deferred ART initiation (2008-2012), the proportion of participants reporting CLS-D was similar when compared between randomized arms at year 1 [48]. Many observational studies have assessed the association between ART and sexual behaviour among people with diagnosed HIV , including two meta-analyses [29,32] and some studies in low/middle income countries [41,43,45]. The vast majority found no association of ART use or viral suppression with CLS-D, or found ART was in fact associated with lower levels of CLS-D. A few studies reported different findings overall, or in specific subgroups or analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from some observational studies have suggested that, in some contexts or subgroups, condom use may be influenced by knowledge of viral suppression [24][25][26][27][28][29]. However, in most studies, overall, levels of CLS-D were similar or lower among people on ART compared with those not on ART (or among people with undetectable compared with detectable viral load) [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Two randomized trials have provded data on this issue [47,48]; neither supports the hypothesis that ART use leads to increased CLS-D.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sabe-se que um importante fator de risco para Infecções Sexualmente Transmissíveis (IST) e que aparece associado ao aumento de casos de HIV em HSH na América Latina é o sexo anal, insertivo ou receptivo, sem o uso do preservativo (Julio et al, 2015;Pinheiro, Calazans, & Ayres, 2013;Wade, Harper, & Bauermeister, 2017). Estudos desenvolvidos no Brasil destacam que mais de 30% dos HSH entrevistados referiram um uso inconsistente de preservativo nos últimos 6 meses (Rocha, Gomes, Camelo, Ceccato, & Guimarães, 2013) e 12 meses (Brignol & Dourado, 2011).…”
unclassified